#NoFilter: The Censorship of Artistic Nudity on Social Media - Gabriella Mas (Washington University Journal of Law & Policy, 2017)
This Note evaluates the state of artistic expression and prohibitions against obscenity in the age of online social media. Mas traces the trajectory of obscenity laws in the U.S. and the development of social media as a means of both expression and communication around the world. The Note then discusses potential solutions for conflicts that arise from established first amendment jurisprudence and the prevalence of social media as a private entity that regulates a significant portion of public discourse. The Note concludes private social media websites that hold themselves as public forums should be held to federal obscenity laws in order to protect expression and communication online in light of the current Miller standard.
Keywords: Artistic Expression; Prohibitions; Obscenity; Social Media; First Amendment; Public Forum; Miller Standard